Biometric‐based efficient medical image watermarking in E‐healthcare application. Issue 3 (1st February 2019) - Aparna, Puvvadi; Kishore, Polurie Venkata Vijay
Abstract : Information hiding is particularly used for security applications to protect the secret message from an unauthorised person. Due to the tremendous development of the Internet and its usage, the issue of protection over the internet is increasing. Under such a condition, transforming the information from the transmitter to the receiver requires more security. Accordingly, in my previous research, an efficient medical image watermarking technique in E‐healthcare application using a combination of compression and cryptography algorithm was proposed. The system only gives confidentiality and reliability. To overcome the problem, the authors propose a biometric‐based on an efficient medical image watermarking in E‐healthcare application, which produces a system for authentication, confidentiality, and reliability of the system. The proposed system utilises the fingerprint biometric for authentication, cryptography process for confidentiality, and reversible watermarking for the integrity. Basically, the proposed system consists of two stages such as (i) watermark embedding process and (ii) watermark extraction process. The experiments were carried out on the different medical images with electronic health record and the effectiveness of the proposed algorithm is analysed with the help of peak signal‐to‐noise ratio and normalised correlation.